Validation of the educational technology for diagnosis communication between health professionals and children with cancer (Research, Society and Development, 2023)
Objective: To validate, with experts, an educational technology for communication between health professionals and children with cancer about their diagnosis and treatment process. Methodology: methodological study of validation of educational technology regarding its content and appearance, with quantitative and qualitative analysis of the data. Participated 27 expert judges in pediatric oncology and/or communication of bad news, healthcare professionals. The following domains were considered: Objectives, Relevance, Content, Language, Illustrations, Layout, Motivation and Support material. Results: Quantitative data were analyzed using the Content Validation Index (CVI) with a cutoff 80% and qualitative data were grouped according to domains and discussed in an articulated with the relevant literature in the area, aiming at improving and adapting the material. The educational technology was validated with a total CVI of 94%. Conclusion: The high validity index obtained to the Flor da Raiz Vermelha technology as a mediating strategy so that healthcare professionals can communicate with children with cancer about their diagnosis and treatment process, through a playful and sensitive approach to needs of each child.